2021
DOI: 10.1155/2021/2053795
|View full text |Cite
|
Sign up to set email alerts
|

Facial Emotion Recognition Predicts Alexithymia Using Machine Learning

Abstract: Objective. Alexithymia, as a fundamental notion in the diagnosis of psychiatric disorders, is characterized by deficits in emotional processing and, consequently, difficulties in emotion recognition. Traditional tools for assessing alexithymia, which include interviews and self-report measures, have led to inconsistent results due to some limitations as insufficient insight. Therefore, the purpose of the present study was to propose a new screening tool that utilizes machine learning models based on the scores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 53 publications
(77 reference statements)
1
2
0
Order By: Relevance
“…In line with previous studies [ 6 , 46 , 47 ], we found reduced performance on the overall EK-60F in alexithymic patients. In these patients, left CDT z-scores also correlated with the EK-60F subscore for surprise, which is a predictor of alexithymia [ 47 ]. In contrast, in non-alexithymic patients, sensitivity to heat pain is inversely related to the EK-60F subscore for fear.…”
Section: Discussionsupporting
confidence: 93%
“…In line with previous studies [ 6 , 46 , 47 ], we found reduced performance on the overall EK-60F in alexithymic patients. In these patients, left CDT z-scores also correlated with the EK-60F subscore for surprise, which is a predictor of alexithymia [ 47 ]. In contrast, in non-alexithymic patients, sensitivity to heat pain is inversely related to the EK-60F subscore for fear.…”
Section: Discussionsupporting
confidence: 93%
“…The classification results have been evaluated using four metrics: accuracy (%), sensitivity (%), specificity (%), and F 1‐measure (%) scores. Given the basic statistics of true positive (TP) represents the number of risk‐taking managers detected correctly, true negative (TN) measures the number of risk‐averse managers predicted correctly, false negative (FN) represents the number of risk‐taking managers detected as risk‐averse managers, and false positive (FP) represents the number of risk‐averse managers predicted as risk‐taking managers (Farhoumandi et al., 2021). Therefore, the evaluation metrics can be calculated as follows: Accuracybadbreak=0.33emTP+TNTP+TN+FP+FN$$\begin{equation}{\mathrm{Accuracy\ }} = \ \frac{{{\mathrm{TP}} + {\mathrm{TN}}}}{{{\mathrm{TP}} + {\mathrm{TN}} + {\mathrm{FP}} + {\mathrm{FN\ }}}}\end{equation}$$ Sensitivitybadbreak=TP0.33emTP+FN$$\begin{equation}{\mathrm{Sensitivity\ }} = \frac{{{\mathrm{TP\ }}}}{{{\mathrm{TP}} + {\mathrm{FN}}}}\end{equation}$$ Specifcitybadbreak=TN0.33emTN+FP$$\begin{equation}{\mathrm{Specifcity\ }} = \frac{{{\mathrm{TN\ }}}}{{{\mathrm{TN}} + {\mathrm{FP}}}}\end{equation}$$ Precisionbadbreak=TP0.33emTP+FP$$\begin{equation}{\mathrm{Precision\ }} = \frac{{{\mathrm{TP\ }}}}{{{\mathrm{TP}} + {\mathrm{FP}}}}\end{equation}$$ F1badbreak−measuregoodbreak=0.33em2goodbreak×0.33emprecision×sensitivityprecision+sensitivitygoodbreak=2TP2TP+FP+FN$$\begin{equation}F1 - {\mathrm{measure\ }} = \ 2 \times \ \frac{{{\mathrm{precision}} \times {\mathrm{sensitivity}}}}{{{\mathrm{precision}} + {\mathrm{sensitivity}}}} = \frac{{2{\mathrm{TP}}}}{{2{\mathrm{TP}} + {\mathrm{FP}} + {\mathrm{FN}}}}\end{equation}$$…”
Section: Methodsmentioning
confidence: 99%
“…The classification results have been evaluated using four metrics: accuracy (%), sensitivity (%), specificity (%), and F 1‐measure (%) scores. Given the basic statistics of true positive (TP) represents the number of risk‐taking managers detected correctly, true negative (TN) measures the number of risk‐averse managers predicted correctly, false negative (FN) represents the number of risk‐taking managers detected as risk‐averse managers, and false positive (FP) represents the number of risk‐averse managers predicted as risk‐taking managers (Farhoumandi et al., 2021 ). Therefore, the evaluation metrics can be calculated as follows: …”
Section: Methodsmentioning
confidence: 99%
“…The result shows that the CNN-BiLSTM was 98.75% accurate. Farhoumandi et al (2021) tried to predict alexithymia using a facial emotion recognition model. Several students from the University of Tabriz were selected based Stud.…”
Section: Answers To Rq3mentioning
confidence: 99%
“…We have also observed that many researchers have employed machine learning and deep learning techniques for emotion detection purposes. As reviewed in this research, one of the algorithms that were being used is the SVM which was used by researchers like (Gupta 2018;Farhoumandi et al, 2021;Siam et al, 2022) went ahead and compared the SVM with other algorithms which include KNN, NB, LR, RF and a multilayer perceptron (MLP) algorithm, eventually the MLP outperform the compared machine learning algorithm. Other algorithms used are deep learning algorithms which include the CNN algorithm, which was used by (Punidha et al, 2020;Singh et al2022).…”
Section: Cnn Algorithmmentioning
confidence: 99%